Palaeoecological record of long Eemian series from Kozłów (Central Poland) with reference to palaeoclimatic and palaeohydrological interpretation. (20th September 2022) - Suchora, Magdalena; Kultys, Kamil; Stachowicz-Rybka, Renata; Pidek, Irena A.; Hrynowiecka, Anna; Terpiłowski, Sławomir; Łabęcka, Karolina; Żarski, Marcin
Abstract: In this study, we present the full sequence of Eemian succession from the Kozłów palaeolake – one of the key sites for Eemian Interglacial in this part of Poland. In the paper, previous palynological and diatom assessments were supplemented by further pollen, Cladocera and macrofossil analysis. This enabled detailed reconstruction of a palaeolake functioning under changes of climate and other environmental conditions during MIS 5e. All identified alterations of trophy, depth and aquatic vegetation within the reservoir point to dynamic changes in early stages of lake functioning, relatively stable conditions in mid-Eemian and gradual lake shallowing starting from Caprinus phase. Thus, Kozlów palaeolake joins the noble group of sites with exceptionally well-recognized multi-proxy records of the Eemian Interglacial environment, and has the potential to become a benchmark for this part of Europe.